Control prenatal inadecuado asociado a complicaciones perinatales en el Hospital Nacional Sergio E. Bernales en el periodo enero junio del 2019 - Martínez Laos, Helen Paola (2020)
INTRODUCCION: The problem regarding perinatal complications remains a concern in the health sector, both globally and nationally; and its association with inadequate prenatal control is of a significant proportion. The main complications for the newborn are prematurity and low birth weight, while in the mother is Preeclampsia. OBJECTIVE: To determine the association between inadequate prenatal control and perinatal complications at the Sergio E. Bernales National Hospital in the period January to July 2019. METHODS AND ANALYSIS PLAN: A retrospective, observational, analytical, case - control study was conducted. It was performed with a total of 507 patients, made up of newborns treated in the Neonatology service of the Sergio E. Bernales National Hospital in the period from January to June 2019. This sample consisted of 169 cases, including pregnant women and / or newly born who presented some complication in the perinatal period, and by 388 controls formed by those who did not present such complications. The data analysis is performed in the SPSS program, to obtain the value p, OR and 95% CI. RESULTS: The cases were 169 and the controls 338. Of the cases, 68.6% presented some complications compared to 20.7% of the controls. Likewise, 37.2% patients presented inadequate prenatal controls. And it was found that not having adequate prenatal control implies an approximately 9 times greater risk of presenting some complication (CI: 5,820-14,034). Conclusions: An inadequate prenatal control is a risk factor to present some perinatal complication.